On the Weight Reduction of Metals due to Temperature Increments (Global Journal of Science Frontier Research, 2012)
Based on E = mc 2 , Einstein remarked that an increase of E in the amount of energy must be accompanied by an increase of E/c 2 in mass; and thus the increased temperature would lead to an increased weight. However, based on the recently discovered charge-mass interaction, it is predicted instead that a heated up matter would have a reduced weight. Experimentally, Fan, Feng, and Liu found that the weights of six kinds of metals including gold, silver, copper, nickel, aluminum, and iron decrease as the temperature increases from 100 degree to 600 degree. Nevertheless, Fan et al. regard these weight reductions as a result of modifying the mass in Newtonian gravity, but not due to a new repulsive force as the case of charged capacitors. Thus, they could have inadvertently created a problem with the notion of negative mass. Moreover, this would not help solving the NASA space-probe anomaly. Therefore, it is necessary to clarify that their experimental results are essentially due to a repulsive charge-mass interaction and that the theories of Galileo, Newton and Einstein are inadequate.
Keywords: pioneer anomaly; repulsive force; charge-mass interaction; charged capacitors; E = mc2